PEMANFAATAN ASSET BASED COMMUNITY DEVELOPMENT BAGI DISABILITAS - Sukanda, Rosyikin (Sekolah Tinggi Kesejahteraan Sosial (STKS) Bandung, 2016)
AbstractThis paper emerged asset-based approach as a way to drive community to see a reality, to appreciate what worked well in the past, and to use what we have to get to bring a change for disability people. The purpose of this study was to determine how the use of the asset-based community development for disability in Bandung. This research was qualitative descriptive of asset utilization based on community development for disability in Bandung. Through visits and observation at social institutions, itexplained the implementation of asset utilization based community development for the disability communities. The results of the institutional changes supported the service on Children with Disabilities especially for RBM and the Communication Forum for Children Families with disability. It alsochanged the lives of children. It brought a novelty that through the approchthe AdD could access basic services such as therapy, health, and education. Key words: asset-based community development, disability, AdD, Community-based Rehabilitation AbstrakMakalah ini mengangkat pendekatan berbasis asset sebagai cara mengajak masyarakat melihat realitas, mengapresiasi apa yang bekerja dengan baik di masa lampau, dan menggunakan apa yang telah dimiliki untuk membawa perubahan bagi difabilitas. Tujuan makalah ini mengetahui bagaimana penerapan asset based community development bagi disabilitas di Kota Bandung. Penelitian ini bersifat deskriptif kualitatif tentang pemanfaatan asset based community development bagi disabilitas studi kasus di Kota Bandung. Melalui kunjungan institusi yang mendukung layanan pada Anak dengan Disabilitas (AdD) dalam hal ini Rehabilitasi Berbasis Masyarakat (RBM) dan Forum Komunikasi Keluarga Anak dengan Kedisabilitasan. Selain itu juga perubahan atas kehidupan anak-anak. AdD dapat mengakses pelayanan dasar seperti terapi, kesehatan, dan pendidikan. Kata kunci: Asset Based Community Development, Disabilitas, Anak dengan Disabilitas, Rehabilitasi Berbasis Masyarakat